Anti-inflammatory activity test of matoa fruit peel ethanol extract (Pometia pinnata J. R. Forst. & G. Forst.) on carrageenan edema model of white rats - Irene Eunike Tanod; A. M. Muslihin; Lukman Hardia (Institute of Computer Science (IOCS), 2026)
Background: Inflammation is a protective biological response to tissue injury or infection; however, excessive inflammation may lead to tissue damage and chronic disease. Matoa fruit peel (Pometia pinnata J.R.Forst. & G.Forst.) contains bioactive compounds, including Flavonoids, saponins, tannins, and phenolics, which are known to have anti-inflammatory properties, are present in the plant. Objective: This study sought to assess the anti-inflammatory efficacy of the ethanol extract derived from the matoa fruit peel through the utilization of a carrageenan-induced paw edema model in male white rats. Methods: In an experiment, we used male white rats (Rattus norvegicus) and split them into five groups. We had a negative control, a positive control, and three treatment groups. The treatment groups got ethanol extract at different doses—100, 200, and 300 mg/kg of body weight. To get the inflammation going, we gave them a 1% carrageenan injection under their skin. Paw edema volume was measured periodically using a plethysmometer to determine the anti-inflammatory effect. Results: The initial volume of edema of the whole group was homogeneous (0.06 ± 0.00–0.01 mL). Ethanol extract of matoa fruit peel at doses of 100, 200, and 300 mg/kgBB showed anti-inflammatory activity by gradually reducing edema until the 6th hour. The dose of 100 mg/kgBB provided the highest edema inhibition effect (42.06 ± 8.36%), followed by the 300 mg/kgBB dose (41.27 ± 13.75%) and 200 mg/kgBB (31.75 ± 2.75%), while positive control showed the largest inhibition (61.11 ± 9.62%). Statistical analysis showed that all treatment groups differed significantly from negative controls (p < 0.05), but still had lower effectiveness than positive controls.Conclusion:Ethanol extract of matoa fruit peel demonstrates promising anti-inflammatory activity in carrageenan-induced male white rats and may serve as a potential natural source for anti-inflammatory drug development. Further studies are needed to identify the active compounds, clarify the molecular mechanisms, and evaluate the extract's safety.